2013
DOI: 10.1107/s0021889813020438
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reciprocal space mapping of diffuse scattering for the study of stacking faults in semipolar (\bf 11{\overline 2}2) GaN layers grown from the sidewall of anr-patterned sapphire substrate

Abstract: Three-dimensional reciprocal space mapping of semipolar (11{\overline 2}2) GaN grown on stripe-patternedr-plane (1{\overline 1}02) sapphire substrates is found to be a powerful and crucial method for the analysis of diffuse scattering originating from stacking faults that are diffracting in a noncoplanar geometry. Additionally, by measuring three-dimensional reciprocal space maps (3D-RSMs) of several reflections, the transmission electron microscopy visibility criteria could be confirmed. Furthermore, similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…8 The high relative intensity of NBE to BSF related emission (NBE to BSF intensity ratio of 2.8), and the narrow linewidth of the GaN bandedge emission of 14 meV indicate high microstructural quality, especially when compared to semipolar or nonpolar GaN on planar sapphire substrates. 8,9,26 Further, techniques such crystal shaping for defect bending and blocking 16,27 and use of in-situ grown interlayers 28,29 have shown additional improvement in microstructural quality with growth on patterned sapphire is possible.…”
mentioning
confidence: 98%
“…8 The high relative intensity of NBE to BSF related emission (NBE to BSF intensity ratio of 2.8), and the narrow linewidth of the GaN bandedge emission of 14 meV indicate high microstructural quality, especially when compared to semipolar or nonpolar GaN on planar sapphire substrates. 8,9,26 Further, techniques such crystal shaping for defect bending and blocking 16,27 and use of in-situ grown interlayers 28,29 have shown additional improvement in microstructural quality with growth on patterned sapphire is possible.…”
mentioning
confidence: 98%
“…(5) Quantification of the BSF density using Monte Carlo simulations of the streak profile was established and described in detail in previous work by Barchuk et al (2011), who have developed the underlying model based on a Monte Carlo simulation approach which determines the BSF densities from the diffuse scattering along the streak for semipolar (1122) GaN (Lazarev et al, 2013). In our previous work, the PL measurements of the semipolar (1122) GaN provided evidence of a strong defect-correlated luminescence at 3.43 eV attributed to BSFs of type I 1 (Lazarev et al, 2013;Scholz et al, 2014;Schwaiger et al, 2010). Furthermore, the luminescence peak appearing at 3.32 eV, assigned to BSFs of type I 2 , is significantly weaker than the band of 3.43 eV originating from BSFs of type I 1 for the two surface orientations studied, 1011and 1122 (Scholz et al, 2014).…”
Section: X-ray Diffraction Setup and Reconstruction Of 3d-rsms From Tmentioning
confidence: 99%
“…Such structures typically suffer from huge densities of stacking faults (Scholz et al, 2014, and references therein), so the analysis and optimization of such structures with respect to these defects is strongly required. Typically, the basal plane stacking fault (BSF) density in nonpolar structures is larger than 10 5 cm À1 (Moram, Johnston, Hollander, Kappers & Humphreys, 2009;Barchuk et al, 2011), while semipolar GaN grown on prepatterned sapphire substrates has revealed a BSF density at least two orders of magnitude lower (Scholz et al, 2014;Lazarev et al, 2013). Romanov et al (2006) have calculated the total polarization discontinuity for In x Ga 1Àx N layers coherently strained to GaN for crystallographic orientations varying between polar c plane ( = 0 ) and nonpolar ( = 90 ) for different indium contents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations